Pengembangan Website Online Berbasis Blended Learning Untuk Meningkatkan Penguasaan Konsep Mata Pelajaran IPA - Nukhbatul Bidayati Haka; Siti Makrupah; Bambang Sri Anggoro (Universitas Lampung, 2020)
Learning support facilities in AL-Azhar 3 Junior High School in Bandar Lampung are sufficient for the learning process of students, but not yet optimally in utilizing technology for the learning process. This study aims to determine the development and feasibility of online media websites based on blended learning to improve the mastery of the concepts of Natural Sciences in Biology in the online form. This type of Research and Development (RD). The feasibility of the product can be seen from the results of the percentage of validators with the criteria